Metagenomic analysis reveals gestational diabetes mellitus-related microbial regulators of glucose tolerance - Wu, Yanxin; Bible, Paul W.; Long, Sizhe; Ming, Wai-kit; Ding, Wenjing; Long, Yuhang; Wen, Xiaofeng; Li, Xifang; Deng, Xiuli; Deng, Yuhua; Guo, Shixin; Doçi, Colleen L.; et al. (Acta diabetologica, 2020)
Aims Recent studies have suggested a possible association between microbiota and gestational diabetes (GDM). However, the results are inconsistent. Our objective was to investigate further the relationship between GDM and microbiota and verify the potential microbial marker. Methods Two complementary approaches were used for the demonstration. First, we compared the gut microbial composition of 23 GDM patients and 26 non-GDM ethnically Chinese Han pregnant women, by using whole-metagenome shotgun sequencing of their stool samples collected at the third trimester. Second, we used Q-PCR (quantitative polymerase chain reaction) to evaluate the gut microbial composition in the stool samples from another cohort of 150 Chinese pregnant women (113 Control and 37 GDM), to further confirm the potential microbial marker. Results The gut microbiota of GDM women show lower albeit not statistically significant ( p = 0.18) alpha diversity at the species level than non-GDM women. However, the species-level beta-diversity or between-sample diversity measured by Bray–Curtis distance shows significant differences ( p < 2.2e−16) between the two groups. The species Bacteroides dorei positively correlated with both OGTT (oral glucose tolerance test) 0-Hour ( p = 0.0099) and OGTT 1-Hour ( p = 0.0070). There is a similar trend between Bacteroides sp. 3_1_33FAA and both OGTT 0-Hour ( p = 0.014) and OGTT 1-Hour ( p = 0.0101) response variables. The species Alistipes putredinis negatively correlated with OGTT 1-Hour ( p = 0.0172) and OGTT 2-Hour ( p = 0.0147). Q-PCR validation further confirmed the association between the glucose tolerance loci of Bacteroides dorei and OGTT response. Conclusions Gut microbiome is related to the diabetic status of Chinese women during pregnancy. Specific species such as Bacteroides dorei associate with glucose response and could be potential monitoring and therapeutic microbial markers for GDM.